Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To find the limit of the expression
[tex]\[ \lim_{k \to -2} \frac{k^3 + 8}{k^2 - 4}, \][/tex]
let's work through the problem step-by-step:
1. Factorize the numerator and denominator:
The numerator [tex]\( k^3 + 8 \)[/tex] can be factorized using the sum of cubes formula, which states that [tex]\( a^3 + b^3 = (a + b)(a^2 - ab + b^2) \)[/tex]. Here, [tex]\( a = k \)[/tex] and [tex]\( b = 2 \)[/tex], so:
[tex]\[ k^3 + 8 = k^3 + 2^3 = (k + 2)(k^2 - 2k + 4). \][/tex]
The denominator [tex]\( k^2 - 4 \)[/tex] can be factorized using the difference of squares formula, which states that [tex]\( a^2 - b^2 = (a - b)(a + b) \)[/tex]. Here, [tex]\( a = k \)[/tex] and [tex]\( b = 2 \)[/tex], so:
[tex]\[ k^2 - 4 = (k - 2)(k + 2). \][/tex]
2. Rewrite the limit expression with the factored forms:
Substitute the factored forms into the original expression:
[tex]\[ \frac{k^3 + 8}{k^2 - 4} = \frac{(k + 2)(k^2 - 2k + 4)}{(k - 2)(k + 2)}. \][/tex]
3. Simplify the expression by canceling common factors:
We can cancel the common factor [tex]\( k + 2 \)[/tex] in the numerator and the denominator:
[tex]\[ \frac{(k + 2)(k^2 - 2k + 4)}{(k - 2)(k + 2)} = \frac{k^2 - 2k + 4}{k - 2}. \][/tex]
4. Evaluate the limit of the simplified expression:
Now, we consider the limit of the simplified expression as [tex]\( k \)[/tex] approaches [tex]\(-2\)[/tex]:
[tex]\[ \lim_{k \to -2} \frac{k^2 - 2k + 4}{k - 2}. \][/tex]
Substitute [tex]\( k = -2 \)[/tex] into the simplified expression:
[tex]\[ \frac{(-2)^2 - 2(-2) + 4}{-2 - 2} = \frac{4 + 4 + 4}{-4} = \frac{12}{-4} = -3. \][/tex]
So, the limit is:
[tex]\[ \lim_{k \to -2} \frac{k^3 + 8}{k^2 - 4} = -3. \][/tex]
[tex]\[ \lim_{k \to -2} \frac{k^3 + 8}{k^2 - 4}, \][/tex]
let's work through the problem step-by-step:
1. Factorize the numerator and denominator:
The numerator [tex]\( k^3 + 8 \)[/tex] can be factorized using the sum of cubes formula, which states that [tex]\( a^3 + b^3 = (a + b)(a^2 - ab + b^2) \)[/tex]. Here, [tex]\( a = k \)[/tex] and [tex]\( b = 2 \)[/tex], so:
[tex]\[ k^3 + 8 = k^3 + 2^3 = (k + 2)(k^2 - 2k + 4). \][/tex]
The denominator [tex]\( k^2 - 4 \)[/tex] can be factorized using the difference of squares formula, which states that [tex]\( a^2 - b^2 = (a - b)(a + b) \)[/tex]. Here, [tex]\( a = k \)[/tex] and [tex]\( b = 2 \)[/tex], so:
[tex]\[ k^2 - 4 = (k - 2)(k + 2). \][/tex]
2. Rewrite the limit expression with the factored forms:
Substitute the factored forms into the original expression:
[tex]\[ \frac{k^3 + 8}{k^2 - 4} = \frac{(k + 2)(k^2 - 2k + 4)}{(k - 2)(k + 2)}. \][/tex]
3. Simplify the expression by canceling common factors:
We can cancel the common factor [tex]\( k + 2 \)[/tex] in the numerator and the denominator:
[tex]\[ \frac{(k + 2)(k^2 - 2k + 4)}{(k - 2)(k + 2)} = \frac{k^2 - 2k + 4}{k - 2}. \][/tex]
4. Evaluate the limit of the simplified expression:
Now, we consider the limit of the simplified expression as [tex]\( k \)[/tex] approaches [tex]\(-2\)[/tex]:
[tex]\[ \lim_{k \to -2} \frac{k^2 - 2k + 4}{k - 2}. \][/tex]
Substitute [tex]\( k = -2 \)[/tex] into the simplified expression:
[tex]\[ \frac{(-2)^2 - 2(-2) + 4}{-2 - 2} = \frac{4 + 4 + 4}{-4} = \frac{12}{-4} = -3. \][/tex]
So, the limit is:
[tex]\[ \lim_{k \to -2} \frac{k^3 + 8}{k^2 - 4} = -3. \][/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.